Avaliação específica no judô: uma revisão de métodos - Detanico, D.; dos Santos, S. G. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2012)
The aim of this study was to analyze the judo specific tests present in the literature, including the variables obtained from these and their use as performance markers in judo matches. To develop of this study we considered original articles indexed from 1990 to 2011, using electronic data bases Scopus®, SciELO®, ScienceDirect® (Elsevier) and PubMed®. The keywords used for research were: judo, performance, aptitude tests and their combinations. After analyzing the articles deemed eligible, we elected four tests (studies) that considered all criteria: a) Special Judo Fitness Test (SJFT), b) endurance test of Azevedo et al. (2007), c) Uchikomi Fitness Test - UFT and d) Santos Test. All tests have the judo motor skills for the identification of physiological variables, however, its use depends of the researcher`s purpose. The SJFT can be used for the identification of anaerobic and aerobic capacity as well as being able to induce glycolytic and aerobic demand similar inthe judo match. The Azevedo et al. endurance test needs a validation process based in the gold-standard to maximal lactate steady state to be a reliable tool in the obtain the aerobic capacity. The UFT and the Santos Test reproduce some judo match characteristics, but still need more original studies to be considered as performance markers.